Decline in duration, satisfaction and sleep quality among informal caregivers of stroke survivors, 18-months post-stroke - Teixeira, F (2021)
Background. Data on stroke caregivers’ sleep is scarce. We aimed to assess changes in duration, satisfaction and sleep quality among informal caregivers of stroke survivors. Methods. Informal caregivers (n = 126) of stroke survivors hospitalized between September 2018 and August 2019 in the 12 Stroke Units of the North of Portugal were invited to participate in the study, 18 months’ post-stroke. Sociodemographic and sleep characteristics (duration, satisfaction and quality) were collected through structured questionnaires. Odds ratios and 95% confidence intervals (95%CI) were estimated through logistic regression, adjusted for age and sex. Answers to open-ended questions were synthetized using content analysis. Results. Due to care provision, informal caregivers reported sleeping, on average (SD), significantly less hours (7.0 (1.7) vs. 6.4 (1.8); p < 0.001). Since its beginning, caregivers’ satisfaction with their sleep decreased approximately 30%. Changes in sleep quality, namely difficulties in falling asleep and constant interruptions during sleep, were reported by almost 70% of caregivers. Only 6.4% described the prescription of medication to sleep after beginning care provision. Participants who returned to work (adjusted OR = 0.34; 95%CI:0.16-0.76) and with a monthly income above 1000€ (adjusted OR = 0.29; 95%CI:0.13-0.66) were less likely to report changes in sleep quality. Conclusions. A decline in duration, satisfaction and sleep quality of informal caregivers of stroke survivors, 18 months’ post-stroke, was observed. Changes in sleep quality revealed socioeconomic inequalities, highlighting the need to prevent adverse health outcomes related to sleep disturbance.